Corrigendum to "Micro-foundations of congestion and pricing: A game theory perspective" [Transp. Res. Part A 39 (2005) 691–704]. (August 2015) - Levinson, David; Janusch, Nicholas
Abstract: This paper amends "Micro-foundations of Congestion and Pricing: A Game Theory Perspective" Levinson (2005), correcting the calculated tolls and Nash equilibria predicted for a three-player game.